2011
DOI: 10.1016/j.ajo.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Graft Thickness, Graft Folds, and Aberrations After Descemet Stripping Endothelial Keratoplasty for Fuchs Dystrophy

Abstract: Purpose To determine whole eye high-order aberrations (HOAs) in pseudophakic eyes after Descemet stripping endothelial keratoplasty (DSEK) for Fuchs dystrophy, and to establish relationships between graft thickness, HOAs, and visual acuity. Design Cross-sectional study. Methods Whole eye HOAs were measured in pseudophakic eyes at intervals through 24 months after DSEK, and in otherwise healthy pseudophakic control eyes implanted with the same type of spherical intraocular lens. Wavefront errors were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 28 publications
3
37
0
1
Order By: Relevance
“…67,95,112 Chamberlain et al found that anterior corneal HOAs were higher after DSAEK than in age-matched controls, showing that the underlying disease process and / or the surgical technique (i.e. corneal incisions) have a tangible effect on the anterior cornea.…”
Section: Anterior Cornea and Hoasmentioning
confidence: 99%
See 3 more Smart Citations
“…67,95,112 Chamberlain et al found that anterior corneal HOAs were higher after DSAEK than in age-matched controls, showing that the underlying disease process and / or the surgical technique (i.e. corneal incisions) have a tangible effect on the anterior cornea.…”
Section: Anterior Cornea and Hoasmentioning
confidence: 99%
“…36,71 Graft folds affect the posterior corneal surface, and are believed to be due to a mismatch in curvature between the host stroma and anterior graft surface. 112 Letko et al reported uneven graft thickness and graft folds in the visual axis of the donor graft in cases of unsatisfactory visual acuity after DSAEK. 71 Seery et al found that thicker grafts were associated with more graft folds, which in turn correlated moderately and significantly with HOAs at 24 months (r=0.44).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of endothelial graft thickness on visual acuity in DSAEK is controversial, with some authors reporting better results with thinner grafts and others finding no correlation (10)(11)(12)(13)(14)(15). However, studies evaluating this subject have either focused on relatively thick grafts (160-170 µm) or on grafts prepared by manual dissection (11)(12)(13)(14)(15). When grafts having less than 130 µm are evaluated, a positive correlation between thickness and visual acuity is obtained (9,10), suggesting that an effect may exist under a certain thickness.…”
Section: Methodsmentioning
confidence: 99%